Accurate modeling of photovoltaic systems for studying the transient effects of lightning strikes - Ibrahim Hetita (Elsevier, 2022)
The integration of renewable energy sources (RES) as an alternative source of energy is increasing continuously. This is due to various advantages of RES over traditional energy sources, as they are clean sources and never run out. One of the most important RES is solar photovoltaic (PV) systems, which have attracted more attention in recent years. Lightning overvoltages are considered the main cause of PV modules damage. Hence, designing an effective and reliable lightning protection system (LPS) is important to improve the lightning performance of PV systems and reduce hazards. This requires accurate modeling of the PV system under lightning conditions. Some previous researches used high accuracy modeling methods such as the finite definite time-domain (FDTD) or the method of moments (MOM). However, these techniques require a high computation burden and have some complexity. Although the partial element equivalent circuit method (PEEC) gives a high accuracy model with less complexity, very few researchers focused on using it for PV systems modeling. This paper introduces a high accuracy model of the PV system during the lightning occurrence using the PEEC method, considering the coupling effects and the influence of metal frame, which were not considered in previous researches. The transient overvoltages at different points are calculated taking into account changing the lightning striking point, the existence of PV frame, and changing soil resistivity. From the simulation results, the transient overvoltages are increasing with increasing the soil resistivity value. In addition, the induced voltage has a maximum value at the striking point and decreases by moving away from it. Moreover, the existence of the metal frame causes an increase in the induced overvoltages values; hence the LPS requirements will change. The grounded legs of the mounting system are considered an important factor in determining the voltage values, where the points connected to the grounded leg will have the lowest voltages values. On the other hand, the transient overvoltages obtained with the existence of the mutual coupling are larger than those obtained when neglecting the mutual coupling. The results confirmed that it is better to consider the mutual coupling to achieve an effective LPS.